Public Forum by Undergraduate Medical Students During Clinical Postings: A Way to Improve the Communication Skill - Sumedha Sharma; Aruna Nigam (Indian Journal of Medical Specialities)
Introduction: Excellent communication skills are essential to the practice of medicine as good doctor–patient communication is necessary to elicit information from the patient to arrive at an accurate diagnosis. Aim: The aim of this study was to assess the improvement in the communication skills of undergraduate medical students using public forum as a tool. Methodology: A total of 80 students of 5th-semester MBBS were invited to participate in public forum on the topic of “contraception.” Their communication skills were assessed using the Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) assessment of communication skills tool. Each student performed four public forums over 2 months, one every fortnight. Each student delivered 15 min talk once in 2 weeks in front of a group of patients regarding the different contraceptive methods. The assessment of communication skill was done twice, i.e., they were assessed at the first and after the fourth public forum. Paired t-test was applied to assess the improvement in communication skill. Results: The mean score on RANZCOG assessment at the first public forum was 11.92 ± 3.89 and after the fourth public forum was 19.75 ± 6.13 (P < 0.00). An overall improvement in scores was 22.3%. There was a statistically significant improvement in the scores for all the points on the RANZCOG checklist. All the students felt more confident after the public forums. Conclusion: Involving students in small public forums (or patient education programs) helps in improving communication skills and can, in turn, be of great help improving the personality of the future medical professionals as well as in the development of better health-care providers.